2019
DOI: 10.1007/s11325-019-01897-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of positional obstructive sleep apnea (POSA) in patients with severe OSA

Abstract: We assessed the prevalence of Positional Patients (PPs) and the main predictors of positional dependency in severe Obstructive Sleep Apnea (OSA). A simulated effect of Positional Therapy (PT) vs. Continuous Positive Airway Pressure (CPAP) was also assessed. Methods Polysomnographic recordings of 292 consecutive patients with severe OSA (Apnea-Hypopnea Index (AHI) ≥ 30) who slept > 4h and had ≥ 30 min sleep in both supine and lateral positions were assessed. PPs had a supine AHI / lateral AHI ratio ≥ 2 and Non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
0
13
0
7
Order By: Relevance
“…There exists evidence in the literature for differences in POSA prevalence among differing ethnicities, most notably a potential increased prevalence among patients of Asian ethnicity compared to Caucasian, which may be related to differences in the craniofacial structure. [11][12][13][14][15][16]29 Further evidence from direct correlation studies however is lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There exists evidence in the literature for differences in POSA prevalence among differing ethnicities, most notably a potential increased prevalence among patients of Asian ethnicity compared to Caucasian, which may be related to differences in the craniofacial structure. [11][12][13][14][15][16]29 Further evidence from direct correlation studies however is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…44 Our study, in line with the majority of previous literature reporting on prevalence of POSA and the severity of OSA, found the prevalence of POSA was higher in patients with milder OSA and reduced with increasing severity of the OSA. [12][13][14]16,28,29,37,45 It is likely that as the disease severity progresses the positional variability of the obstructive events is lost, and events start being observed in all body positions. 46,47 This may also be the reason that POSA is more commonly observed in patients with lower BMI, as BMI generally correlates with OSA severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that in severe OSA some patients could gain even greater benefits from positional therapy compared with using CPAP with suboptimal adherence (Oksenberg, Gadoth, Töyräs, & Leppänen, 2019). In the weight-gain group, simulated positional therapy was able to compensate for a weight-related increase in the AHI.…”
Section: Ta B L Ementioning
confidence: 95%
“…Several potential factors, including anthropometric measurement, clinical characteristics, and polysomnographic parameters, have been identified to help in differentiating between positional and non-positional OSA. Although there were some discrepancies regarding the difference between positional and non-positional OSA, most of the studies found that positional OSA tends to be younger, non-obese and are associated with mildmoderate OSA rather than severe OSA [3,7,8].…”
Section: Introductionmentioning
confidence: 99%